THE INFLUENCE OF ENTREPRENEURIAL MOTIVATION AND ENTREPRENEURIAL CHARACTERISTICS ON THE SUCCESS OF RONO DANGE MICRO-ENTERPRISE IN LERO VILLAGE, SINDUE DISTRICT, DONGGALA REGENCY - Imel Amanda; Lina Mahardiana; Andi Indriani Ibrahim; Moh Ali Murad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of entrepreneurial motivation and entrepreneurial characteristics on the success of rono dange micro-enterprises in Lero Village, Sindue District, Donggala Regency. The study used a quantitative method with an associative approach. The study population consisted of 30 rono dange entrepreneurs and the entire population was sampled through a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 25. The results showed that entrepreneurial motivation had a positive and significant effect on business success with a calculated t value of 3.736 and a significance of 0.001. Entrepreneurial characteristics also had a positive and significant effect on business success with a calculated t value of 3.645 and a significance of 0.001. Simultaneously, entrepreneurial motivation and entrepreneurial characteristics had a positive and significant effect on business success with a calculated F value of 183.857 and a significance of 0.000. The coefficient of determination (R²) value of 0.932 indicates that 93.2% of the variation in business success can be explained by these two independent variables. and the remaining 6.8% is influenced by other variables outside this research model . The results of this study prove that increasing entrepreneurial motivation and entrepreneurial characteristics can increase the success of the rono dange micro-business in Lero Village.